A Survey on students' perception on the effectiveness of online learning in communicative english classes among PKT students (Southeast Asian Journal of Technology and Science, 2023)
The pandemic Covid19 has caused conventional system of education which is focusing on physical classroom and face to face interaction between educators and students to alternately change into virtual learning process. The study was conducted to review on the students’ perception of the effectiveness of online learning in Communicative English class among Polytechnic Kuala Terengganu students. A set of questionnaires was used as a data collection tool to 61 respondents. The sampling was Electrical and Electronics Engineering students who took Communicative English Courses. The data was analysed using SPSS version 20.0. The findings revealed that most of the respondents agreed on the effectiveness of online learning in Communicative English Classes, with the mean value 3.2. The mean score for lecturer-student engagement, students’ concentration and motivation and online assessments were interpreted at medium high level. It concluded that students were having good perception on the effectiveness of online Communicative English class implementation. These findings are significant as to support the lecturers and institution in designing more applicable online teaching and learning approaches. However, it is recommended for further researches in the same area involving more sample of respondents, including the other English courses.